2017
DOI: 10.22302/iribb.jur.mp.v85i1.241
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh biostimulan terhadap pertumbuhan vegetatif tanaman tebu varietas PSJT-941 [Effects of biostimulants on vegetative growth of sugarcane variety PSJT-941]

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 5 publications
2
5
0
2
Order By: Relevance
“…Biostimulant and silica application along with fertilizer increased the growth of sugarcane that can be seen from the addition of the stem length compared to the control. These results are in line with the research done by Putra et al [5], which states that foliar spraying of chitosan-based biostimulant at 1 MAP can stimulate vegetative growth of sugarcane.…”
Section: Analysis Of Biostimulant and Silica Application Effect On Sugarcane Growth Parameterssupporting
confidence: 92%
See 2 more Smart Citations
“…Biostimulant and silica application along with fertilizer increased the growth of sugarcane that can be seen from the addition of the stem length compared to the control. These results are in line with the research done by Putra et al [5], which states that foliar spraying of chitosan-based biostimulant at 1 MAP can stimulate vegetative growth of sugarcane.…”
Section: Analysis Of Biostimulant and Silica Application Effect On Sugarcane Growth Parameterssupporting
confidence: 92%
“…In general, all treatments with the addition of biostimulant and silica (P1, P2, P3, and P4) have a higher Brix value when compared to treatments without the addition of biostimulant and silica (P0). Therefore, the application of biostimulant and silica can increase the total Research conducted by Putra et al [5] showed an increase in Brix value of sugarcane by 11.2% compared to control due to the addition of liquid biostimulants foliar. In addition, there is a close relationship between Brix value and sucrose content (expressed in Pol).…”
Section: Analysis Of Biostimulant and Silica Application Effect On Post-harvest Sugarcane Quality Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…While the number of segments in the stem had significantly increased, that was 40% compared to the control. The provision of biostimulants that can increase vegetative growth was also expected to improve the harvest of sugarcane crops [4].…”
Section: Resultsmentioning
confidence: 99%
“…It improves nutrient absorption efficiency and tolerance of abiotic, thus improving production [3]. Biostimulants increased the growth of sugarcane crops, horticulture, and some food crops [4,5,6,7]. The Biostimulant in this research is made from extracts of seaweed organic matter.…”
Section: Introductionmentioning
confidence: 99%